2014
DOI: 10.1002/cncr.28682
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal impact of patient navigation on equity in colorectal cancer screening in a large primary care network

Abstract: BACKGROUND:The long-term effects of interventions to improve colorectal (CRC) screening in vulnerable populations are uncertain. The authors evaluated the impact of patient navigation (PN) on the equity of CRC prevention over a 5-year period. METHODS: A culturally tailored CRC screening PN program was implemented in 1 community health center (CHC) in 2007. In a primary care network, CRC screening rates from 2006 to 2010 among eligible patients from the CHC with PN were compared with the rates from other practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 42 publications
(52 reference statements)
2
75
0
Order By: Relevance
“…25,26 RESULTS Figure 1 presents a PRISMA flow diagram demonstrating the systematic review process and the final 15 articles that were included in the narrative review. The 15 studies were subdivided according to type of cancer screening that was evaluated, including breast (combined with other cancers), [27][28][29][30][31] colorectal cancer, [32][33][34][35][36][37][38][39][40][41][42][43][44] and cervical cancer, [45][46][47] represented in Table 1. Fifteen non-English languages were evaluated in these studies.…”
Section: Quality Appraisalmentioning
confidence: 99%
See 3 more Smart Citations
“…25,26 RESULTS Figure 1 presents a PRISMA flow diagram demonstrating the systematic review process and the final 15 articles that were included in the narrative review. The 15 studies were subdivided according to type of cancer screening that was evaluated, including breast (combined with other cancers), [27][28][29][30][31] colorectal cancer, [32][33][34][35][36][37][38][39][40][41][42][43][44] and cervical cancer, [45][46][47] represented in Table 1. Fifteen non-English languages were evaluated in these studies.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…45,46 Seven (46 %) were cohort studies. 27,[29][30][31]39,43,47 . All the navigators in the studies assisted patients in navigating the cancer screening (e.g., setting up appointments and making reminder calls) along with providing language services.…”
Section: Quality Appraisalmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Previous studies have demonstrated that several approaches for increasing overall CRC screening and reducing disparities in CRC screening are possible, such as mailed interventions, telephone outreach, and patient navigation. [10][11][12][13][14][15][16][17][18][19][20][21] However, it is unclear whether a pragmatic intervention targeting screening in large healthcare delivery systems with diverse practice types can simultaneously achieve these twin aims of quality and equity improvement. Programs targeting population-level screening rates may actually increase disparities if they are more successful in well-off groups, 13 while interventions meant to improve equity may not increase overall screening rates.…”
Section: Discussionmentioning
confidence: 99%